Are Routine Post-discharge Diuretics Necessary After Pediatric Cardiac Surgery? - Penk, Jamie S.; de Faria, Guilherme Baptista; Collins, Catherine A.; Jackson, Lindsay M.; Porlier, Avaliese L.; Petito, Lucia C.; Marino, Bradley S. (Pediatric cardiology, 2023)
A prospective, one-armed, safety non-inferiority trial with historical controls was performed at a single-center, quaternary, children’s hospital. Inclusion criteria were children aged 3 months–18 years after pediatric cardiac surgery resulting in a two-ventricle repair between 7/2020 and 7/2021. Eligible patients were compared with patients from a 5-year historical period (selected using a database search). The intervention was that “regular risk” patients received no diuretics and pre-specified “high risk” patients received 5 days of twice per day furosemide at discharge. 61 Subjects received the intervention. None were readmitted for pleural effusions, though 1 subject was treated for a symptomatic pleural effusion with outpatient furosemide. The study was halted after an interim analysis demonstrated that 4 subjects were readmitted with pericardial effusion during the study period versus 2 during the historical control (2.9% versus 0.2%, P = 0.003). We found no evidence that limited post-discharge diuretics results in an increase in readmissions for pleural effusions. This conclusion is limited as not enough subjects were enrolled to definitively show that this strategy is not inferior to the historical practice. There was a statistically significant increase in readmissions for pericardial effusions after implementation of this study protocol which can lead to serious complications and requires further study before conclusions can be drawn regarding optimal diuretic regimens.